Influence of Thoracic Kyphosis on Reverse Total Shoulder Arthroplasty Outcomes. Issue 19 (1st October 2021) - Reintgen, Christian; Armington, Samuel; Vigan, Marie; Werthel, Jean-David; Patrick, Matthew; King, Joseph; Wright, Thomas; Schoch, Bradley
Abstract : Introduction: Patient dissatisfaction after primary reverse total shoulder arthroplasty (rTSA) has been reported as high as 9%. In patients with excessive thoracic kyphosis, the scapula protracts and tilts anteriorly, which may lead to early impingement with the acromion and loss of forward elevation. The primary purpose of this study was to evaluate the effect of thoracic kyphosis on overhead ROM after rTSA. Methods: A prospectively collected shoulder registry was retrospectively reviewed for all patients undergoing primary rTSA with a minimum of 2-year follow-up. Preoperative and latest follow-up ROM (forward elevation, abduction, internal rotation, and external rotation), patient-reported outcome measures (SPADI, SST-12, ASES, UCLA, SF-12, and the visual analog scale), and the Constant score were collected. Postoperative radiographs were evaluated for implant loosening and notching. Patients were separated into three groups according to the thoracic kyphosis angle (<25°, 25 to 45°, and >45°) and also analyzed as a continuous variable. The groups were compared using analysis of variance and chi-square tests as indicated. Results: Three hundred five shoulders in 279 patients were reviewed at a mean follow-up of 3.9 years (range 2 to 10 years). Female patients and patients with a history of heart disease were statistically more likely to have increased thoracic kyphosis ( P < 0.05). After surgery, forward elevation and abduction were similar among all groups (<25: 133°, 25 to 45: 132°, >45: 127°; P = 0.199 and <25: 123°, 25 to 45: 122°, >45: 117°; P = 0.330). All other postoperative ROM measurements and all patient-reported outcome measures were also similar, regardless of measured kyphosis. In addition, no association was observed between the degree of thoracic kyphosis and scapular notching ( P = 0.291). Discussion: Despite thoracic kyphosis being a known risk factor for loss of overhead motion in the native shoulder, shoulders with excessive thoracic kyphosis demonstrated similar overhead ROM at early follow-up after primary rTSA. Level of Evidence: III